Educational social software for context-aware learning [ collaborative methods and human interaction - Lambropoulos, Niki , 1966-; Romero, Margarido , 1980- (Information Science Reference, 2010)
"This book examines socio-cultural elements in educational computing focused on design and theory where learning and setting are intertwined"--Provided by publisher.